1998
DOI: 10.1002/(sici)1096-8628(19981102)80:2<133::aid-ajmg8>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Partial trisomy of chromosome 6q: An interstitial duplication of the long arm

Abstract: We report on a 5-year-old girl with a de novo interstitial duplication of chromosome 6q21-q23 and delayed development and speech with distinctive minor facial anomalies including a "carp" mouth. Fluorescence in situ hybridization using a chromosome 6 paint probe confirms that the extra material is of chromosome 6 origin. This further delineates the dup(6q) syndrome and the manifestations due to the specific duplicated chromosomal region involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…These included all 7 familial cases (families K and L) and 4 sporadic cases ( (16,17), and 9 were identified using quantitative PCR of ESTs and STSs from the region (Fig. 1, ID [12][13][14][15][16][17][18][19][20]. Determining the parental origin in 9 of the duplication cases (visible and submicroscopic) was possible by testing both parents using the same method as that used for the probands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These included all 7 familial cases (families K and L) and 4 sporadic cases ( (16,17), and 9 were identified using quantitative PCR of ESTs and STSs from the region (Fig. 1, ID [12][13][14][15][16][17][18][19][20]. Determining the parental origin in 9 of the duplication cases (visible and submicroscopic) was possible by testing both parents using the same method as that used for the probands.…”
Section: Resultsmentioning
confidence: 99%
“…This was in keeping with the 18 cases of maternal dupli-cation of the region, which have been described in the literature as without neonatal diabetes (18), and likewise TND has not been reported in maternal UPD6 (19). One additional case of duplication of 6q and TND has been reported for which the origin of the duplication is unknown (20).…”
mentioning
confidence: 99%
“…Several cases of TNDM were reported to be due to paternal uniparental disomy of chromosome 6 (11)(12)(13) or partial trisomy of chromosome 6q with duplication of the paternal genome (14 -17). Duplications (15) and interstitial deletions (18) of the same region of the maternally inherited chromosome 6 are not associated with the disease. These findings strongly suggest that TNDM results from the overexpression of a paternally expressed, maternally imprinted gene on chromosome 6q.…”
mentioning
confidence: 99%
“…Interstitial 6q duplications are more unusual events and very few studies have reported duplications encompassing the 6q16 and/or 6q21 regions. Among them, five patients from three families have shown tandem 6q duplications [Pratt el al., 1998; Zneimer et al, ; Pazooki et al, ] and six patients from three other families have shown 6q insertional translocations in other chromosomes [Pierpont et al, ; Roland et al, ; Spreiz et al, ]. As far as we know, this is the first report of a pure interstitial 6q15q21 duplication and the second report of a familial maternal 6q duplication.…”
Section: Introductionmentioning
confidence: 62%
“…Apart from ancient SDs and well‐known recurrent microduplications such as the dup(22)(q11.2), new familial interstitial duplications have been reported in several studies[Voullaire et al, ; Mathijssen et al, ; Eussen et al, ; Kowalczyk et al, ; Leach et al, ; Mrasek et al, ; Kang et al, ] and sometimes associated with a normal phenotype [Kowalczyk et al, ; Mrasek et al, ; Kang et al, ]. With regard to 6q duplications, 13 patients have been reported with duplications encompassing the 6q16 and/or 6q21 regions [Chen et al, ; Pierpont et al, ; Roland et al, ; Pratt et al, ; Zneimer et al, ; Pazooki et al, ; Spreiz et al, ], but only one involving the 6q15q21 cytogenetic band [Spreiz et al, ] (Supplementary Table I). Most of these patients have been reported as displaying intellectual disability (11/13), postnatal growth retardation (9/13) and obesity (7/11).…”
Section: Discussionmentioning
confidence: 99%